Irisin: An anti-inflammatory exerkine in aging and redox-mediated comorbidities - Trettel, Caio dos Santos; Pelozin, Bruno Rocha de Avila; Barros, Marcelo Paes; Bachi, André Luis Lacerda; Braga, Pedro Gabriel Senger; Momesso, César Miguel; Furtado, Guilherme Eustáquio; Valente, Pedro Afonso; Oliveira, Edilamar Menezes; Hogervorst, Eef; Fernandes, Tiago (Frontiers in Endocrinology, 2023)
Human beings lead largely sedentary lives. From an evolutionary perspective, such lifestyle is not beneficial to health. Exercise can promote many enabling pathways, particularly through circulating exerkines, to optimize individual health and quality of life. Such benefits might explain the protective effects of exercise against aging and noncommunicable diseases. Nevertheless, the miRNA-mediated molecular mechanisms and exerkine interorgan crosstalk that underlie the beneficial effects of exercise remain poorly understood. In this mini review, we focused on the exerkine, irisin, mainly produced by muscle contraction during adaptation to exercise and its beneficial effects on body homeostasis. Herein, the complex role of irisin in metabolism and inflammation is described, including its subsequent effects on thermogenesis through browning to control obesity and improve glycemic regulation for diabetes mellitus control, its potential to improve cognitive function (via brain derived neurotrophic factor), and its pathways of action and role in aging.